In vitro cytotoxicity study of agave Americana, strychnos Nuxvomica and Areca catechu extracts using MCF-7 cell line - Chetan C Anajwala; Rajesh M Patel; Sanjay L Dakhara; Jitesh K Jariwala (Wolters Kluwer Medknow Publications, 2010)
Research is focusing on the search for new types of natural chemotherapeutic agent that is plant based medicines which are proving to be excellent sources of new compounds. In present research study, an attempt was made to prove cytotoxicity activity of various parts of medicinal plants such as Agave americana, Strychnos nux-vomica and Areca catechu using MCF-7 and Vero cell line. Various parts of the medicinal plants were extracted by soxhlet apparatus using solvents likes methanol and water. By trypan blue dye exclusion method, Viability of MCF-7 and Vero cell lines were 85.50 and 81.13%, respectively. IC 50 value of methanol extract of Agave americana leaves and aqueous extract of Afeca catechu fruits were found to be 545.9 & 826.1 μg/ml by SRB assay and 775.1 & 1461pg/ml by MTT assay, respectively, against MCF-7 cell line. From cytotoxicity study data by SRB and MTT assay, it revealed that methanol extract of Agave americana and aqueous extract of Areca catechu are potent cytotoxic.